The gamification dilemma: balancing fun with fundamentals - Roslan, Muhammad Azril (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Gamification, a term describing the integration of game design elements into non-game contexts, such as education, is one of the most captivating trends in the rapidly evolving field of digital learning. Educators utilise gamification to enhance learning outcomes, engagement, and motivation, as students grow up in a digital environment that is highly saturated with games, social media, and instant gratification. Kahoot! Quizizz, Duolingo, and Classcraft are gamified learning platforms that are gaining prominence due to their ability to transform mundane content into interactive experiences. These tools have been shown to increase student engagement in online environments when used with variety and surprise elements (Raju et al., 2021). These tools use points, badges, leaderboards, challenges, and awards to make education competitive and goal oriented.